2017
DOI: 10.1177/1179299x17690142
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Carcinoembryonic Antigen as a Marker for Predicting the Outcome of Three Cancers

Abstract: BACKGROUNDSerum levels of carcinoembryonic antigen (CEA) are associated with a variety of tumors.OBJECTIVEThis study evaluated the prognostic value of pretreatment serum CEA levels in predicting the outcomes of multiple tumors subjected to treatment.METHODSPrior to therapy, serum samples from 71 prostate, 46 breast, 77 gastric, and 31 pancreatic cancer patients were collected to examine serum CEA levels. The cutoff value for CEA was set as determined by the maximum Youden index. The data were analyzed by the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…21 CA 19-9 and CEA have both been suggested as surrogates of tumor biology among patients with hepatic, pancreatic, biliary and other gastrointestinal malignancies. [33][34][35][36] Ohtsuka et al reported that CA 19-9 was independently associated with ICC prognosis, while Wang et al incorporated both CA 19-9 and CEA in a prognostic nomogram for ICC. 15,16 In a separate study from the Mayo Clinic, Bergquist et al corroborated the prognostic importance of CA 19-9 in a Western cohort of patients with ICC.…”
Section: Discussionmentioning
confidence: 99%
“…21 CA 19-9 and CEA have both been suggested as surrogates of tumor biology among patients with hepatic, pancreatic, biliary and other gastrointestinal malignancies. [33][34][35][36] Ohtsuka et al reported that CA 19-9 was independently associated with ICC prognosis, while Wang et al incorporated both CA 19-9 and CEA in a prognostic nomogram for ICC. 15,16 In a separate study from the Mayo Clinic, Bergquist et al corroborated the prognostic importance of CA 19-9 in a Western cohort of patients with ICC.…”
Section: Discussionmentioning
confidence: 99%
“…CEA is less widely investigated as a prognostic factor than CA15-3 because it has a less positive rate and is more controversial. Some studies have reported that CEA is not a predictor in primary and metastasis breast cancer [ 20 , 21 , 23 , 24 ], but others have reported that high concentrations of CEA were related to a poor prognosis in breast cancer [ 17 , 25 , 26 ]. These above contradictory results of CA15-3 and CEA in breast cancer regarding their prognostic value may be due to small sample sizes, variable study designs, or other biases in each single study.…”
Section: Introductionmentioning
confidence: 99%
“…The glycoprotein, with a half-life of approximately 7 days, was found to be expressed in gastrointestinal and mucosal tissue during fetal development but only minimally expressed in adult tissue (15,16). Further studies showed that it was also overexpressed in adenocarcinomas of varying origin including gastric, hepatic, lung, pancreatic, ovarian and prostate (17)(18)(19)(20)(21)(22)(23)(24). In colon cancer, the specificity and sensitivity of CEA has been shown to vary with advancing tumor stage, with specificity ranging between 37% and 86% in advanced disease, providing a useful means of monitoring disease (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%